Handbook on legal methodology : from objective to method - Kestemont, L. (Lina) (Cambridge : Intersentia, 2018)
Legal scholarship is one of the oldest academic disciplines, and the study of law has been passed on from generation to generation as an implicit 'savoir faire'. It was presumed that all legal scholars understood the methodology of legal research, making its explicit clarification and justification unnecessary. Over the last decade, the lack of an explicit methodological tradition has become problematic due to the growing interdisciplinary collaboration at universities and the increased importance of external funding, often granted by mixed experts panels. It is therefore time for legal scholarship to make its implicit methodology explicit.
Title from publisher's bibliographic system (viewed on 22 Feb 2022).
Keywords: elektronické knihy; electronic books; Law -- Methodology -- Handbooks, manuals, etc